Governed economic development in Europe's northernmost periphery. From company town to industrial diversity? - Marte Bjørnsen; Steinar Johansen (European Regional Science Association (ERSA), 2011)
Svalbard is the northernmost settlement in Europe, situated halfway between northern Norway and the North Pole. Settlement is restricted to Spitsbergen Island and there are two main settlements, the Norwegian town Longyearbyen and the Russian town Barentsburg. In addition, there are a few research stations about the island. Svalbard has been visited by hunters/whalers for centuries but settlement started with the mining industry around 1900. The size of the populations is in part politically determined and has historically varied with the mining activity. Total population is 2500 of which 80 per cent lives in the Norwegian settlement, which also is the administrative centre of Svalbard. In this paper, we analyse the relationships between basic economic activities, other economic activities and population in Longyearbyen. The analysis is based on a yearly panel of establishment data dating from early 1990s. We construct a multiplier model to analyse historical trends as well as future prospects. The economic growth which has taken place the last twenty years is strongly linked to the activity in the mining company but also to growth in other and emerging industries. In the 1990s, the Norwegian government stimulated other economic activities to develop alongside mining to establish a more soundly founded settlement. In particular, higher education, research activities, tourism, and public government have evolved as subsidiary industries. In 2010, sixty per cent of all labour years were performed in these subsidiary industries. Population has grown along with economic activity and more workers bring their families. This again, leads to growth in services of general interest. Today we may see a shift in this unbroken growth trend. The activity level in mining is falling and it remains to see how robust the subsidiary industries are to this changed situation. We have calculated that it takes a more than proportional increase in e.g. research or tourism activities to compensate for loss of employment in the mining industry. The last two years' experience does, however, show an even more markedly negative development in the private sector subsidiary industries.
Keywords: 330